Gen Y Employee Retention: The Interplay of Work-Life Balance, Supervisor Support, and Engagement in Semarang - Nabiel Fadilla, Zulvan; Yuniawan, Ahyar (Universitas Pendidikan Nasional, 2024)
Intention to quit is a critical issue for organizations, as it can disrupt the stability of human resource management and lead to increased turnover rates. This study focuses on Generation Y employees, aged 28-43 years, working in various companies across the manufacturing, service, and trading sectors in Semarang City. Using a quantitative approach with a simple random sampling technique, data were collected from 100 respondents to examine the influence of work-life balance, supervisor support, and employee engagement on intention to quit. The results of hypothesis testing reveal that work-life balance has a positive but insignificant influence on intention to quit, leading to the rejection of H1. This suggests that while work-life balance is important, it may not be a decisive factor in reducing quit intentions among Generation Y employees. On the other hand, supervisor support demonstrates a negative and significant influence on intention to quit, supporting the acceptance of H2. This highlights the crucial role of supportive leadership in retaining employees. Meanwhile, employee engagement shows a negative but insignificant influence on intention to quit, resulting in the rejection of H3. This indicates that while engagement initiatives are beneficial, they may not be sufficient alone to curb quit intentions. Based on these findings, organizations are advised to reevaluate their work-life balance policies, enhance employee engagement programs, and develop comprehensive retention strategies tailored to the needs of Generation Y employees. By addressing these areas, companies can better mitigate quit intentions and foster a more stable and committed workforce.